Psychopath free (expanded edition) eaudiobook Recovering from emotionally abusive relationships with narcissists, sociopaths, & other toxic people. - MacKenzie, Jackson (Tantor Media, 2015)
The psychopath carefully selects the most indifferent and heartbreaking way imaginable to abandon you. They destroy you as a way to reassure themselves that their new target is better. But most importantly, they destroy you because they hate you. They despise your empathy and love, and to destroy you is to temporarily silence the nagging reminder of the emptiness that consumes their soul. Unbeknownst to both of you, this is the beginning of a great adventure... Psychopath Free operates under the assumption that you are not defined by your pain, but instead by the subsequent choices you make along the way. The goal is to make the process a bit more holistic, to provide all the tools you'll need to find validation, self-respect, peace, and love. Psychopath Free will help you out of the darkness so that you can begin making better choices that will forever alter the course of your life. So say farewell to love triangles, cryptic letters, self-doubt, and manufactured anxiety. You are no longer a pawn in the mind games of a psychopath. You are free.